PENGARUH KOMPOS LIMBAH BAGLOG JAMUR TIRAM DAN PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI KERITING (Capsicum annum L.) PADA TANAH GAMBUT PEDALAMAN - Sinaga T. M. T.; Winarti Sih; Asie K. V. (AgriPeat, 2015)
The objectives of this study namely analyze of waste baglog of effect oyster mushrooms compost to growth and yield curly chilli on Peat Land and to find out the doses of waste baglog of oyster mushrooms compost which give the best curly chilli growth and yield. The experimental design used was a completely randomized design factorial (CRD), which consists of two factors treatments. The first factor was giving the waste baglog of oyster mushrooms compost which consists of four levels, namely: control, 100, 200 and 300 gpolybag-1. The second factor was giving the biofertilizer which consists of three levels, namely: control, 40 and 60 gpolybag-1.The results showed that the interaction waste compost baglog oyster mushrooms and biofertilizer only be obtained at the age of two weeks after planting the plant height chilli curls and composting waste baglog oyster mushrooms very significant effect on plant height, stem diameter, days to flowering plants, productive branches, the amount of fruit and fresh weight per plant. Composting 100 g polybag-1 is the best dosage. Biofertilizer application significantly higher only in the high growth of curly chilli plants